2011
DOI: 10.1080/02699931.2010.514711
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and cognitive control in a mixed antisaccade task: Specific effects of depressive rumination

Abstract: Growing empirical evidence suggests that cognitive and affective problems in depression may be a reflection of cognitive control impairments. However, to date, the nature of such impairments is still poorly understood and further investigation of this topic is required to advance current knowledge on the underlying vulnerability factors for depression. Using a mixed antisaccade paradigm, the present study examined if depressive symptoms in general, and more specifically rumination, are related to impairments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 30 publications
4
58
2
Order By: Relevance
“…Past research has reported similar across-valence effects in the association between cognitive processes and rumination – albeit trait rumination – within a dysphoric sample (e.g., De Lissnyder et al, 2012). Moreover, other studies have shown that trait rumination is linked with difficulty inhibiting neutral or non-emotional material (e.g., De Lissnyder, Derakshan, De Raedt, & Koster, 2011). It is therefore possible that the association between rumination and cognitive control deficits may not be specific to negative material but instead may be found across the board.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has reported similar across-valence effects in the association between cognitive processes and rumination – albeit trait rumination – within a dysphoric sample (e.g., De Lissnyder et al, 2012). Moreover, other studies have shown that trait rumination is linked with difficulty inhibiting neutral or non-emotional material (e.g., De Lissnyder, Derakshan, De Raedt, & Koster, 2011). It is therefore possible that the association between rumination and cognitive control deficits may not be specific to negative material but instead may be found across the board.…”
Section: Discussionmentioning
confidence: 99%
“…In the anti-saccade task, participants are requested to inhibit their reflexive tendency to orient their attention toward an abrupt cue. Similar to the NAP task, when the cue is emotional, the task can serve to measure inhibition of emotional content (e.g., De Lissnyder et al, 2011). …”
Section: Inhibition Of Negative Content As a Shared Process In Ruminamentioning
confidence: 99%
“…The opposite pattern has emerged for rumination. Several studies using the NAP and the anti-saccade tasks have shown that ruminators have difficulty inhibiting emotional content (e.g., De Lissnyder et al, 2011), even when controlling for levels of depressive symptoms (Joormann, 2006; Zetsche and Joormann, 2011; but for discrepant findings see Goeleven et al, 2006). In line with these behavioral findings, investigators have identified rumination-related patterns of brain activation, such as a higher functional connectivity between the left striatum and the left inferior frontal gyrus (IFG), a region that has been associated with inhibition (Kühn et al, 2013).…”
Section: Inhibition Of Negative Content As a Shared Process In Ruminamentioning
confidence: 99%
“…The study of Mahlberg et al [14] showed that patients with depression had longer reaction times (RT) than controls in prosaccade tasks, suggesting that a psychomotor retardation affecting reflexive eye movement could characterize some depressive symptoms. The study conducted by De Lissnyder et al [15] reported that dysphoric subjects had longer RT than controls in the antisaccade task. Globally, these results highlight the need to distinguish between basic reflexive components evaluated by prosaccade tasks and more elaborated executive processes involved in the inhibition required by the antisaccade task.…”
Section: Introductionmentioning
confidence: 99%